A fluid-structure interaction modelling of roof mounted renewable energy installations in low rise buildings for extreme weather and typhoon resilience. Issue 1 (March 2020) - Jay Pantua, Conrad Allan; Calautit, John Kaiser; Wu, Yupeng
Abstract: Super typhoon Haiyan made landfall in the Philippines last 2013 where an estimated 1.1 million homes were damaged. There was massive roofing damage in the houses due to strong winds. With the increasing number of roof-mounted renewable energy installations, there is a clear need to review the current systems to respond to future climactic events. The current approach for building performance analysis under typhoon wind loads involves a lot of wind tunnel tests, full scale testing and finite element modelling which is heavily reliant on wind tunnel data which are costly and time consuming. Current renewable energy mounting technologies with its different installation methods, and mounting locations consequently affected by wind loads differently. Using the proposed framework, this study evaluated solar panels attached to the gabled roof of a single detached low-rise building. The stress and deformation of the structure and the panels was determined using the typhoon's Atmospheric Boundary Layer flow simulation. Building energy simulation was used to determine the appropriate site orientation to maximise solar energy generation. Results show areas of high failure rate in the panels in the 0 degree wind angle direction and in the panels closer to the edge. Maximum solar energy generation was determined at the 90 degree site orientation.